Study on minerals status of dairy cows and their supplementation through area specific mineral mixture in the state of Jharkhand - B. M. Bhanderi; Ajay Goswami; M. R. Garg; Saikat Samanta (Journal of Animal Science and Technology, 2016)
Abstract Background Deficiency of macro and micro-minerals in the ration of dairy cows adversely affects growth, milk production and reproduction efficiency. It is essential to examine mineral concentrations in feeds offered to dairy cows in practical farms. Methods Two villages from each taluka were selected at random for taking representative samples of feeds, forages and hair. Within the village, help was sought from village milk producers and district animal husbandry officer for identification of 4 to 5 farmers and collection of representative samples. All the samples were processed and analyzed for chemical composition as well as major macro and micro-minerals, using Inductively Coupled Plasma-Optical Emission Spectrometer. Results Ca content in wheat straw (0.29%), crushed maize (0.02%) and wheat bran (0.12%) was found to be below the critical level (0.30%). The P content in concentrate ingredients was high (0.26–0.96%), but low in dry roughages (0.06–0.12%). Cereal straws (0.14%) and grains (0.12%) were deficient in Mg. Feeds and forages were found to be adequate in K (1.50%). Cereals straws were found to be deficient in S (0.11%). Greens were good source of Cu (12.02 ppm). Wheat straw was found to be low in Zn (18 ppm), but high in Mn (225 ppm) and Fe (509 ppm). Local grasses and azolla green were found to be rich source of Co (>1.00 ppm). Se (0.63 ppm) was present in appreciable quantities in most of the feedstuffs. Conclusions From the present study, it was apparent that the feeds and forages available in the state of Jharkhand may not meet the requirements for Ca, P, Mg, Cu, Zn and Co in order to sustain a milk production of ~10 kg/day. Therefore, it is necessary to supplement these deficient minerals through area specific mineral mixture in the ration of dairy cows for improving productivity and reproduction efficiency.